Production of high-performance textiles via pioneering strengthening approach using starch nanoparticles. (September 2020) - Mostafa, Khaled; Ameen, Heba; Morsy, Mahmoud; el-ebiassy, Amal; El-Sanabary, Azza; Adel, Mohamed; Salah, Ali
To minimize the serious defects of durable press finishing of cellulosic textiles with respect to the great loss in strength properties, new pioneering strengthening approach of cotton fabric based on our previously prepared starch nanoparticles of size around 80–100 nm was used. For this purpose, cotton fabrics were treated with different concentrations of starch nanoparticles via coating technique using pad-dry-cure method, at which the starch nanoparticles are attached to the fabrics with the use of a padder adjusted to appropriate pressure and speed, followed by drying and curing. Fabric stiffness, surface roughness, tensile strength, elongation at break, abrasion resistance, wrinkle recovery angles, add-on %, and degree of whiteness as well as durability of treated fabrics were fully explored. SEM was used for detecting the change in surface morphology of reinforced coated fabric. The results obtained reflect the following findings: (a) all fabric performance like tensile strength, stiffness, wrinkle recovery angle, abrasion resistance and add on % were improved for coated fabrics with starch nanoparticles in comparison with untreated fabric, except that of surface roughness; (b) SEM confirmed the change in surface morphology of cotton fabric after reinforcement treatment using starch nanoparticles; (c) the dry wrinkle recovery angle and tensile strength of cotton fabrics treated in presence of 30 g/l starch nanoparticles are slightly decreased after 10 washing cycles as compared with untreated fabric; and (d) starch nanoparticles introduce an advance in textile finishing with respect to the above-mention fabric performance except that of surface roughness.